The Cordyceps Genus as a Potential Source of Bioactive Compounds for Adjuvant Cancer Therapy: A Network Pharmacology Approach - Jose Luis Gonzalez-Llerena; Daniela Treviño-Almaguer; Jesus Alejandro Leal-Mendez; Gael Garcia-Valdez; Arely Guadalupe Balderas-Moreno; Michel Stéphane Heya; Isaias Balderas-Renteria; María del Rayo Camacho-Corona; Bryan Alejandro Espinosa-Rodriguez (Pharmaceuticals)
Background/Objectives: Cancer remains one of the leading causes of mortality globally, underscoring the need for novel therapeutic strategies capable of targeting multiple molecular pathways simultaneously. Natural products, particularly fungal-derived metabolites from the genus Cordyceps, represent promising candidates due to their diverse biological activities. Although previous studies have indicated the anticancer potential of Cordyceps species, systematic characterization of their molecular targets has been limited. This study aimed to comprehensively identify and evaluate Cordyceps metabolites as potential multitarget anticancer agents through a network pharmacology approach. Methods: A total of 129 metabolites previously reported in the literature from polar aqueous, alcoholic, and non-polar extracts of Cordyceps were compiled and chemically classified using ChemMine tools. Structure-based target prediction and pathway enrichment analyses were performed to investigate their potential biological targets. Predicted molecular targets were cross-referenced with differentially expressed genes in breast, colorectal, and lung cancers to identify hub proteins. Molecular docking simulations were conducted to assess binding affinities of metabolites to key oncogenic targets, and SwissADME was utilized for pharmacokinetic profiling. Results: The analysis revealed that Cordyceps metabolites targeted critical oncogenic pathways, including cell cycle regulation, DNA replication, and apoptosis. Hub proteins such as TYMS, AURKA, and CDK1 were identified as primary targets. Docking simulations highlighted metabolites such as cordycepsidone A, jiangxienone, and flazin, demonstrating binding affinities comparable or superior to clinically used inhibitors. Pharmacokinetic profiling identified several metabolites with favorable drug-like properties, supporting their potential as lead compounds. Conclusions:Cordyceps extracts contain structurally diverse metabolites capable of modulating multiple cancer-relevant molecular targets, providing a robust foundation for their development into multitarget anticancer therapies. This integrative network pharmacology approach underscores the potential of fungal metabolites in oncology drug discovery.